PENGARUH SELF-EFFICACY TERHADAP PROFESIONALISME ANGGOTA KEPOLISIAN DAERAH (POLDA) DAERAH ISTIMEWA YOGYAKARTA DENGAN SUBJECTIVE WELL-BEING SEBAGAI VARIABEL KONTROL - Ignatius Geovani Rosantono; Alimatus Sahrah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine: 1) the effect of self-efficacy on professionalism which is positive and significant for members of the Regional Police in the Special Region of Yogyakarta, 2) the influence of self-efficacy on professionalism which is significant with subjective well-being as a control variable on members of the Regional Police in the Special Region Yogyakarta. The sample are 259 respondents. The data collection method uses a self-efficacy scale, a professionalism scale, and a subjective well-being scale. Data analysis used bivariate analysis and partial analysis. The results found 1) there is a positive influence between self-efficacy and professionalism of members Regional Police with a correlation coefficient of 0.645 and a Sig. value of 0.00, 2) there is a significant influence of self-efficacy on professionalism with subjective well-being as a control variable in the number of members of the Regional Police in the Special Region of Yogyakarta is 0.437 which is located at the interval of 0.41 – 0.70 in the